Oral Antibiotic Management of Acute Osteomyelitis of the Hand: Outcomes and Cost Comparison to Standard Intravenous Regimen. (July 2021) - Henry, Mark; Lundy, Forrest H.
Background: Acute, direct inoculation osteomyelitis of the hand has traditionally been managed by intravenous antibiotics. With proven high levels of bone and joint penetration, specific oral antimicrobials may deliver clinical efficacy but at substantially lower cost.Methods: Sixty-nine adult patients with surgically proven acute, direct inoculation osteomyelitis of the hand were evaluated for clinical response on a 6-week postdebridement regimen of susceptibility-matched oral antibiotics. Inclusion required gross purulence and bone loss demonstrated at the initial debridement and radiographic evidence of bone loss. Excluded were 2 patients with extreme medical comorbidities. There were 53 men and 16 women with a mean age of 46 years. Mean follow-up was 16 weeks (±10). The cost model for the outpatient oral antibiotic treatment was intentionally maximized using Walgreen's undiscounted cash price. The cost model for the traditional intravenous treatment regimen was intentionally minimized using the fully discounted Medicare fee schedule.Results: All patients achieved resolution of osteomyelitis by clinical and radiographic criteria. In addition, 7 patients underwent successful subsequent osteosynthesis procedures at the previously affected site without reactivation. The mean postdebridement direct cost of care per patient in the study cohort was $482.85, the cost of the antibiotic alone. The postdebridement direct cost of care per patient on a regimen of vancomycin 1.5 g every 12 hours via peripherally inserted central catheter line was $21 646.90.Conclusions: Acute, direct inoculation osteomyelitis of the hand can be successfully managed on oral antibiotic agents with substantial direct and indirect cost savings.